Chronopolitics: public events and the temporalities of state power in Mozambique - Concalves, Euclides (My University, 2012)
This thesis examines state organised public events as a way to understand the nature and modalities of state power in contemporary Mozambique. My research is based on 18 months of ethnographic fieldwork in the districts of Inharrime and Zavala, in the Southern Province of Inhambane. During this period I interviewed and followed the everyday work of state officials and bureaucrats and observed public meetings, political rallies, inauguration ceremonies, celebrations of commemorative dates and public holidays, state visits by “high dignitaries” and resulting orientações - authoritative written and oral documents that are generally taken by local state officials and bureaucrats as guidelines for the implementation of government policies and programs. I also conducted archival research at the district and provincial level from where I obtained some of the regulatory documents and reports referred to in my analysis. I argue that state organised public events produce a chronopolitics upon which rests the reproduction of the state. The research highlights three temporalities that are constitutive of such chronopolitics. The first temporality I have called the “time of agitation” in which the quiet days of the routine bureaucratic practices are punctuated by the nhima-nhima (agitation) caused by visits of “high dignitaries.” Such visits constitute occasions for the performance of state visibility and the presentation of hierarchies. This is done through the marshalling of crowds to participate in “warm receptions” and “mass rallies” for the visiting “high dignitaries.” It is also during visits of “high dignitaries” that state officials mark the territory by displaying state symbols, disseminating official discourse and presenting high ranking officials as the embodiment of the state. The second temporality I have termed the “time of performativity.” Here the analysis focuses on platforms set up for public rallies on which state officials, bureaucrats and members of the public negotiate what can be said and how it can be said. It is also on these platforms that government declared policies and programs are performatively accomplished by “talking” about them. The third temporality is the “time of provisionality”, a result of state officials and bureaucrats’ strategic use of timing. Here the key resources are orientações. In everyday bureaucratic practice, the continuous revision of these regulatory documents determines the pace of policy implementation. While for analytical purposes I have distinguished three temporalities, my ethnographic accounts point to the intersections between them to reveal a mode of state power I have termed chronopolitics. In doing so, this thesis provides an analytical counterpoint to dominant instrumental readings of power that see political action only in terms of the negotiation of consent. The results of my interpretation of state organized public events show that neither state officials and bureaucrats nor members of the public work only with instrumental interests of that kind in view. The immediate effect occasioned by the staging and participation in state organised public events is the inscription of state officials, bureaucrats and members of the public alike in the temporalities of the state.
Ph.D. University of the Witwatersrand, Faculty of Humanities (Anthropology), 2012